2014
DOI: 10.1172/jci75429
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation alters cellular and humoral responses to yellow fever 17D vaccine

Abstract: Background. Defining the parameters that modulate vaccine responses in African populations will be imperative to design effective vaccines for protection against HIV, malaria, tuberculosis, and dengue virus infections. This study aimed to evaluate the contribution of the patient-specific immune microenvironment to the response to the licensed yellow fever vaccine 17D (YF-17D) in an African cohort. Conclusion.Together, these results demonstrate that an activated immune microenvironment prior to vaccination imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
152
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 51 publications
7
152
1
Order By: Relevance
“…As previously shown, innate immunity induced by YF vaccination is generally important for the vaccine response outcome (18,42,43). In this article, we showed that we could classify vaccinees according to their age by multivariate analysis of major innate cell types.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As previously shown, innate immunity induced by YF vaccination is generally important for the vaccine response outcome (18,42,43). In this article, we showed that we could classify vaccinees according to their age by multivariate analysis of major innate cell types.…”
Section: Discussionmentioning
confidence: 69%
“…Because induction of innate immunity by YF vaccination has been shown to critically influence elicitation of subsequent effector responses (18,42,43), we assessed absolute numbers of seven circulating innate cell types (Supplemental Fig. 1B) and evaluated them on the peak of innate immunity at day 4 by PCA.…”
Section: Reduced Early DC Responses In the Elderly Are Associated Witmentioning
confidence: 99%
“…The effects could lead to enhanced immune responses to other pathogens and vaccines. With respect to vaccines, there is increasing concern regarding poor immunogenicity in rural areas of developing countries (28,29); therefore, any measure to alleviate hyporesponsiveness would have a major public health impact. It is also important to consider the long-standing evolutionary coexistence between humans and helminths, the disturbance of which might lead to the emergence of pathological conditions (30).…”
Section: Discussionmentioning
confidence: 99%
“…Muyanja et al showed that the cellular and humoral immune responses to the highly efficacious live yellow fever vaccine YF-17D in East African individuals were substantially lower than those of European volunteers treated identically (30). Prior to vaccination, the East African volunteers presented an increased activated immune microenvironment with higher frequencies of exhausted and activated natural killer cells, differentiated B and T cells, and proinflammatory monocytes (30).…”
Section: Discussionmentioning
confidence: 99%